Prognostic Significance of T‐Wave Amplitude in Lead aVR on the Admission Electrocardiography in Patients with Anterior Wall ST‐Elevation Myocardial Infarction Treated by Primary Percutaneous Intervention - Ayhan, Erkan (Ann Noninvasive Electrocardiol, 2012)
Background: T‐wave positivity in aVR lead patients with heart failure and anterior wall old ST‐segment elevation myocardial infarction (STEMI) are shown to have a higher frequency of cardiovascular mortality, although the effects on patients with STEMI treated with primary percutaneous coronary intervention (PCI) has not been investigated. In this study, we sought to determine the prognostic value of T wave in lead aVR on admission electrocardiography (ECG) for in‐hospital mortality in patients with anterior wall STEMI treated with primary PCI. Methods: After exclusion, 169 consecutive patients with anterior wall STEMI (mean age: 55 ± 12.9 years; 145 men) undergoing primary PCI were prospectively enrolled in this study. Patients were classified as a T‐wave positive (n = 53, group 1) or T‐wave negative (n = 116, group 2) in aVR based upon the admission ECG. All patients were evaluated with respect to clinical features, primary PCI findings, and in‐hospital clinical results. Results: T‐wave positive patients who received primary PCI were older, multivessel disease was significantly more frequent and the duration of the patient's hospital stay was longer than T‐wave negative patients. In‐hospital mortality tended to be higher in the group 1 when compared with group 2 (7.5% vs 1.7% respectively, P = 0.05). After adjusting the baseline characteristics, positive T wave remained an independent predictor of in hospital mortality (odds ratio: 4.41; 95% confidence interval 1.2–22.1, P = 0.05). Conclusions: T‐wave positivity in lead aVR among patients with an anterior wall STEMI treated with primary PCI is associated with an increase in hospital cardiovascular mortality.